If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 16y = 7x + y Solving 4x + 16y = 7x + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 4x + -7x + 16y = 7x + -7x + y Combine like terms: 4x + -7x = -3x -3x + 16y = 7x + -7x + y Combine like terms: 7x + -7x = 0 -3x + 16y = 0 + y -3x + 16y = y Add '-16y' to each side of the equation. -3x + 16y + -16y = y + -16y Combine like terms: 16y + -16y = 0 -3x + 0 = y + -16y -3x = y + -16y Combine like terms: y + -16y = -15y -3x = -15y Divide each side by '-3'. x = 5y Simplifying x = 5y
| x^2-216= | | 5w+3+w= | | 3/4*3*5 | | an=-2+(n-1) | | y=x^2-5x-9 | | 7x+y=4x+16y | | 5d^2-10d+h=0 | | (y^4/-2z^2)^4 | | X^2+15x+56.25=26.25 | | 5x-5x=200 | | 9=26+3 | | 4-11=17 | | 6f=6f-24 | | g^2-12gh+35h^2=0 | | 5x-25+x+13=180 | | C=4-3X-4Y+2X^2+3Y^2+XY | | logx^2-3logx=-2 | | d^2=490 | | 2b+3(3b+1)=52 | | -3/4x72 | | -4+24=-24 | | d^2-2d+3h=9 | | 1-7+10=0 | | 2b^3/b^2 | | 4x^2-8x-35=0 | | 3x+(x+5)=-3 | | 3x^2-25+2=10 | | 4lnx=4nx | | -1/2x-4/5 | | -1.47=j+-4 | | 4nx=4lnx | | 1.1+.75x+2=3.1+.75x |